A Proposed Organizational Structure Model of The Civil Service Training Institute to Enhance The Quality of Workforce in The Public Sector - Choocheep, Kanokwan; Usaho, Chayapim; Siribanpitak, Pruet (Scholar: Human Sciences, 2016)
The present research applied a descriptive research method aiming at exploring the current status and desirable status of the organizational structure model of the Civil Service Training Institute (CSTI), and proposing such model to enhance the quality of workforce in the public sector. It employed a case study of CSTI under The Civil Service Commission, Thailand. Informants were 35 CSTI’s government officials (71.43 percent), 80 clients from 46 organizations. Interviews were undertaken with 15 experts about policy/strategic vision of management and development of workforce in the public sector, roles and functions towards the organizational structure model of CSTI. Assessment was made on the appropriateness and feasibility of the drafted model. A focus group discussion was carried out among 8 experts to consider the draft model. Research instruments included a questionnaire, interview issues, and model appropriateness and feasibility assessment. Statistical analysis involved frequency, percentage, mean, standard deviation, Priority Need Index (PNImodified) and content analysis. Results revealed that the overall status of the organizational structure model as currently practiced was at moderate level (x = 3.08, S.D. = 0.93), while the desirable status was at high level (x = 4.16, S.D. = 0.78). For the organizational structure model of CSTI to enhance the quality of workforce in the public sector, it adopted an integrated model of PAM Organizational Structure Model (Professional Adhocracy and Matrix Organizational Structure Model).